Efficient Modified Estimators for the Population Mean Using Auxiliary Variables - Dansawad, Napattchan (Naresuan University Journal: Science and Technology (NUJST), 2022)
This paper presents three modified estimators to estimate the population mean by utilizing information on auxiliary variables under simple random sampling without replacement (SRSWOR). Motivation for the proposed estimators is based on Yadav et al. (2019). Furthermore, the expressions for bias and mean squared error (MSE) of proposed estimators were obtained and compared with other relevant existing estimators through theoretical and empirical studies. It is shown that the proposed estimators perform better than other estimators. Keywords: Modified estimators, Auxiliary variable, Bias, MSE